The influence of comorbid depression and overweight status on peripheral inflammation and cortisol levels. Issue 14 (18th October 2022) - McLaughlin, Anna P.; Nikkheslat, Naghmeh; Hastings, Caitlin; Nettis, Maria A.; Kose, Melisa; Worrell, Courtney; Zajkowska, Zuzanna; Mariani, Nicole; Enache, Daniela; Lombardo, Giulia; Pointon, Linda; ,; et al.
Abstract: Background: Depression and overweight are each associated with abnormal immune system activation. We sought to disentangle the extent to which depressive symptoms and overweight status contributed to increased inflammation and abnormal cortisol levels. Methods: Participants were recruited through the Wellcome Trust NIMA Consortium. The sample of 216 participants consisted of 69 overweight patients with depression; 35 overweight controls; 55 normal-weight patients with depression and 57 normal-weight controls. Peripheral inflammation was measured as high-sensitivity C-Reactive Protein (hsCRP) in serum. Salivary cortisol was collected at multiple points throughout the day to measure cortisol awakening response and diurnal cortisol levels. Results: Overweight patients with depression had significantly higher hsCRP compared with overweight controls ( p = 0.042), normal-weight depressed patients ( p < 0.001) and normal-weight controls ( p < 0.001), after controlling for age and gender. Multivariable logistic regression showed that comorbid depression and overweight significantly increased the risk of clinically elevated hsCRP levels ⩾3 mg/L (OR 2.44, 1.28–3.94). In a separate multivariable logistic regression model, overweight status contributed most to the risk of having hsCRP levels ⩾3 mg/L (OR 1.52, 0.7–2.41), while depression also contributed a significant risk (OR 1.09, 0.27–2). There were no significant differences between groups in cortisol awakening response and diurnal cortisol levels. Conclusion: Comorbid depression and overweight status are associated with increased hsCRP, and the coexistence of these conditions amplified the risk of clinically elevated hsCRP levels. Overweight status contributed most to the risk of clinically elevated hsCRP levels, but depression also contributed to a significant risk. We observed no differences in cortisol levels between groups.